Ultrasound in labor: clinical practice guideline recommendation by the World Association of Perinatal Medicine (WAPM) and the Perinatal Medicine Foundation (PMF) - Giuseppe Rizzo; Tullio Ghi; Wolfgang Henrich; Boris Tutschek; Rasha Kamel; Christoph Lees; Ilenia Mappa; Mariya Kovalenko; Wai-Lam Lau; Torbjorn Moe Eggebo; Reuven Achiron; Cihat Şen (Perinatal Journal, 2022)
This recommendation document follows the mission of the World Association of Perinatal Medicine (WAPM) in collaboration with the Perinatal Medicine Foundation (PMF). We aim to bring together groups and individuals throughout the world for standardization to implement the ultrasound evaluation in labor ward and improve the clinical management of labor. Ultrasound in labor can be performed using a transabdominal or a transperineal approach depending upon which parameters are being assessed. During transabdominal imaging, fetal anatomy, presentation, liquor volume, and placental localization can be determined. The transperineal images depict images of the fetal head in which calculations to determine a proposed fetal head station can be made.